Small states, smart solutions : improving connectivity and increasing the effectiveness of public services - Favaro, Edgardo (Directions in development. Public sector governance., 2008)
"Small States, Smart Solutions: Improving Connectivity and Increasing the Effectiveness of Public Services examines how some small states use international trade and telecommunications technology to outsource services such as justice, banking supervision, public utilities regulation, high-quality medicine, and education. Sourcing these services internationally poses unique challenges but also opens broad opportunities. The eight case studies in this book, based on interviews with government officers and citizens, describe pioneering initiatives undertaken by some small states to better the quality of life of their citizens."--Jacket